Case Report: A Deletion Variant in the DCAF17 Gene Underlying Woodhouse-Sakati Syndrome in a Chinese Consanguineous Family - Chen, Guangmin; Zhou, Ling; Chen, Qimou; Wang, Juan; Jiang, Peng; Shen, Rufei; Long, Min; Zhou, Houdi (Frontiers in Genetics, 2021)
Woodhouse-Sakati syndrome is a rare neuroendocrine disease characterized by hair loss, hypogonadism, diabetes, hearing loss, and extrapyramidal syndrome,which is usually caused by mutations in the DCAF17 gene in close relatives.DCAF17 gene plays an important role in mammalian gonadal development and infertility.The first cases were six Saudi Arabian patients from two highly inbred families reported in 1983(1). Up to now, less than 100 WSS patients were reported, and no case was reported in China. The patient introduced in this case also comes from a close relative marriage family. The main symptoms of the patient are alopecia and gonadal agenesis.Other symptoms such as hearing loss,mental retardation,hyperglycemia are remarkable, and these symptoms often can be observed in WSS patients.Without a definite diagnosis after 10 years of seeking medical advice, she came to our hospital for medical treatment.We noticed she had symptoms of WSS,we also noticed that her brother had similar symptoms to her. We performed a genetic study and fingered out DCAF17 mutation in the patient and her younger brother, which confirmed the diagnosis of WSS. The genetic study also showed that the mutation gene comes from their healthy first-cousin’s parents with recessive mutation genes.